Pemberian Eceng Gondok (Eichhornia crassipes ), Indigofera sp dan Kangkung (Ipomea sp) sebagai Hijauan pada Ransum Kalkun Berbasis Dedak Padi dan Ransum Komersial terhadap Performa dan Kadar Kolesterol Daging: The Use of Eichhornia crassipes, Indigofera sp and Ipomea sp. as Forage in Turkey Rations on Performance and Meat Cholesterol - G P Lestari; W Hermana; D M Suci (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2020)
The aim of this research was to measure the effect of diet contained water hyacinth (Eichhornia crassipes), Indigofera (Indigofera sp.), and water spinach (Ipomoea spp.) on the performance and cholesterol of turkey meat. A total of twelve male turkeys 40 weeks old with average body weight of 4798±551.78 g were reared for six weeks. This research used a Completely Randomized Design. The dietary diet treatments were consisted of 38% rice bran, 35% commercial diet, and 27% forages which consisted of E. crassipes (R1), Indigofera sp. (R2), and Ipomea spp. (R3). The variables measured were performance (feed consumption, final body weight, body weight gain, feed conversion ratio, percentage of abdominal fat, carcass percentage and breast meat cholesterol levels. The results showed that E.crassipes, Indigofera sp., and Ipomea spp. in turkeys’diet did not affect on feed consumption, final body weight, body weight gain, feed conversion ratio, carcass percentage, and percentage of abdominal fat. Cholesterol levels of turkey breast meat in the Indigofera dietary treatment was produced the lowest relative cholesterol levels followed by Ipomoea sp and water hyacinth (Eichhornia crassipe) dietary treatments. The average cholesterol level of turkey breast meat ranges from 23- 47 mg 100 g-1. It was concluded that E.crassipes, Indigofera sp., and Ipomea spp. can be used as an alternative ingredient for adult turkey diet.